Mushroom House Monitoring System Using Internet of Things (IoT) - Mohd Hishamuddin, Muhammad Hafizuddin; Ubin, Aizan (Evolution in Electrical and Electronic Engineering, 2022)
This paper aims to enable people to understand that Internet of Things (IoT) helps humans in any kind of agriculture activities such as monitoring, controlling, adjusting the environment and update real time data. Most agriculture plantings are based on traditional farming and demand a lot of human work processes. Therefore, this project which involves the development of a Mushroom house monitoring kit and automatic control temperature and humidity that can overcome this problem. The works in this project involve the development of a monitoring kit with a control system using an Arduino board as the microcontroller and NODE MCU ESP 32 as the open source IoT platform firmware. The Arduino is programmed to monitor the temperature and humidity of the mushroom house. After receiving the data, Arduino will control the DC fan turning on and off automatically depending on the data received by the sensor. In addition, to make sure the surrounding of the mushroom house is conducive for mushroom cultivation, a water level system serves to channel the water below the mushroom growing kit from reserve water tank. The most important thing in this project, is that the system can update the real time data to the cloud via Wi-Fi. User can access the cloud platform (Thingspeak) using a computer or gadget as long as the internet connection is available. The results for this project show that the data of temperature and humidity are changing depending on the weather, this is because when the weather is cloudy and rainy, the reading of humidity can increase to 98% and the temperature can drop below 27ºC. Furthermore, the preliminary experimental results demonstrated that all the system were optimized and success to achieve the objective.